Students’ empathy in the context of extremist risks - V. A. Tupikova; Ya. A. Gudkova; E. G. Ovchinnikov-Lysenko (RUDN journal of Sociology, 2023)
In unstable conditions, the scale of extremism as a form of illegal actions tends to grow. The statistical decrease in the number of extremist crimes was the result of legislative changes. In the risk group, there are primarily young people from 18 to 30 years old, who are more susceptible to psychological pressure from extremist and terrorist organizations, and especially the student youth, who have already begun to escape from parental control but still did not achieve the full adult responsibility. Public calls for extremist acts are based on various social-psychological mechanisms of influence and aim specifically at this age group. A low level of emotional intelligence, empathy and psychological well-being is essential for entering an extremist environment. In January- February 2022, a survey was conducted to test the hypothesis of a relationship between the level of empathy and propensity to violent extremism. The article presents the results of this survey, such as the lack of direct relationship between the level of empathy and the age. The survey’s unexpected result is that the general level of boys’ empathy is higher than that of girls, and girls are more likely to be extremist when they have a higher level of empathy. Thus, an increasing level of the youth’s empathy seems to be a way to prevent extremist behavior withing a comprehensive program but not a universal strategy for countering youth extremism. The article can become a basis for an effective pedagogical strategy to prevent extremism and to reduce the youths’ risks of being involved in it. The developed approach should take into account the gender peculiarities of empathy, which influence the manifestations of violent extremism.